2014
DOI: 10.3892/etm.2014.1854
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning improvement effects of ulinastatin on brain injury following cardiopulmonary resuscitation

Abstract: Abstract. The aim of the present study was to determine the effects of ulinastatin (UTI) on brain injury in rats subjected to cardiopulmonary resuscitation (CPR) following asphyxial cardiac arrest (CA) and identify the underlying mechanisms. In total, 100 healthy male Wistar rats were randomly divided into control and treatment groups (n=50). After 4 min of asphyxial CA, all the rats were immediately subjected to CPR. The treatment group animals were administered 15 mg/kg UTI at the onset of resuscitation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Our recent study further demonstrated that systemic administration of UTI can attenuate amplification of central pro-inflammatory cytokine (PIC) signal pathway in a rat model of cerebral ischemia induced by CA thereby leading to improvement of neurological severity score, brain tissue edema and survival (Jiang et al 2016). Consistent with this result, UTI has been reported to attenuate neuronal nuclear factor (NF)-κB and PICs and further improve neural functions, and inhibition of PICs leads to downregulation of apoptotic signals (Sui et al 2014. These data indicate the beneficial role played by UTI in alleviating cerebral ischemia reperfusion injury.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Our recent study further demonstrated that systemic administration of UTI can attenuate amplification of central pro-inflammatory cytokine (PIC) signal pathway in a rat model of cerebral ischemia induced by CA thereby leading to improvement of neurological severity score, brain tissue edema and survival (Jiang et al 2016). Consistent with this result, UTI has been reported to attenuate neuronal nuclear factor (NF)-κB and PICs and further improve neural functions, and inhibition of PICs leads to downregulation of apoptotic signals (Sui et al 2014. These data indicate the beneficial role played by UTI in alleviating cerebral ischemia reperfusion injury.…”
Section: Introductionsupporting
confidence: 56%
“…This prior study has also shown that stabilizing HIF-1α significantly attenuates increases of Caspase-3 and TUNEL evoked by induction of CA, and thus improves neurological deficits and neuronal edema (Liu et al 2016). In particular, recent studies further suggest that systemic administration of UTI plays a protective role in regulating neurological deficits observed in CA rats via central PIC mechanisms (Sui et al 2014).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, antibiotic treatment is hampered by the nagging problem of drug resistance. Several clinical studies have demonstrated that linezolid, an effective anti-inflammatory and anti-infective drug, is effective in the treatment of severe pneumonia, while ulinastatin restrains proinflammatory factors and mitigates multiple inflammatory responses [9][10][11][12]. In this study, 98 elderly patients with severe pneumonia were chosen as subjects for investigation of the clinical effect of combined use of linezolid and ulinastatin on the patients.…”
Section: Introductionmentioning
confidence: 99%